First, we need to move the constant term to the right side:
x^2 - 6x = 7
x^2 - 6x + 9 = 7 + 9 (adding (6/2)^2 = 9 to both sides)
(x - 3)^2 = 16
Now we take the square root of both sides (remembering to include both the positive and negative square roots):
x - 3 = ±4
x = 3 ± 4
Rounding to the nearest hundredth, we get:
x = 7.00 or x = -1.00
Therefore, the answer is D) x=7, -1.
Solve the equation by completing the square. Round to the nearest hundredth. X^2 - 6x = 7
A) x=7, 1
B) x=-7, 1
C) x=-7, -1
D) x=7, -1
1 answer